OTT PLATFORMS AND MAINSTREAM MEDIA PATRONAGE IN ENUGU: A DIGITAL ENTERTAINMENT ASSESSMENT - H. Eze, Uchenna; Chiahalam Apeh, Andrew; Lamai Ochanya, Mercy (African Journal of Social and Behavioural Sciences, 2024)
This study is titled OTT Platforms and Mainstream Media Patronage in Enugu: A Digital Entertainment Assessment, aims to examine the influence of Over-The-Top (OTT) platforms on the patronage of mainstream media channels in Enugu, Nigeria. Survey results from 395 respondents show a significant preference for OTT platforms, driven by smartphone use and perceived convenience. It recommended among others that media organizations in Enugu should adopt OTT platforms to meet the entertainment demands of the increasing number of smartphone users, as OTT platforms significantly influence mainstream media channels; that mainstream media houses in Enugu are to incorporate the attributes of OTT Platforms into their daily operation to attract more viewership.